Uncommon foreign body in the hypopharynx: A case report. Issue 26 (June 2018) - Chen, Guowei; Luo, Yizhen; Pan, Hongguang; Teng, Yishu; Liang, Zhenjiang; Li, Lan
Abstract: Rationale: Pharyngeal foreign bodies are a common complaint in emergent cases, and sometimes can be lethal. A large variety of foreign bodies may lodge in the pharynx. We present a case of uncommon foreign body in the hypopharynx. Patient concerns: A 9-month-old boy presented for an hour of crying associated with having congee. No abnormality was revealed in physical examination or cervicothoracic computed tomography (CT) scan. Flexible laryngoscopy showed a size tag on the posterior hypopharyngeal wall. Diagnoses: Foreign body in the hypopharynx. Interventions: The foreign body was removed from the hypopharynx. Outcomes: The patient was discharged after the removal of the foreign body. Lessons: Infants with foreign bodies in the hypopharynx may presented with no obvious clinical manifestation. Pharyngeal foreign bodies may be the potential for disastrous consequences. Otolaryngologists should pay attention to these foreign bodies.